Effect of functional groups on dielectric, optical gas sensing properties of graphene oxide and reduced graphene oxide at room temperature1. Issue 14 (19th February 2015) - Kavinkumar, T.; Sastikumar, D.; Manivannan, S.
<x xml:space="preserve">Abstract</x> Partial reduction of graphene oxide (GO) was accomplished through heat treatment at 110 and 220 °C. Role of various oxygen functional groups in graphene and their gas sensing and electrical properties at room temperature were reported.